Stress-relaxation of crystalline alkali-silica reaction products: Characterization by micro- and nanoindentation and simplified modeling. (1st September 2017) - Zhang, Chi; Sorelli, Luca; Fournier, Benoît; Duchesne, Josée; Bastien, Josée; Chen, Zhao
Highlights: Microindentation test allowed assessing the relaxation behaviour of crystalline in-situ ASR products. The ASR viscous behaviour showed a twofold mechanism possibly related to water movements and interface slips. Nano-indention seems to have characterized the behaviour of few ASR plate-like crystals. The smaller the scale, the more higher are the apparent visco-elastic properties of ASR products. Abstract: Alkali-silica reaction (ASR) is a major issue for the durability of concrete structures worldwide. Fostering recent microindentation works on the elastic property of ASR products, this work aims at further characterizing their viscous property. In particular, this study focuses on the relaxation behaviour of ASR crystalline products which are preferentially formed within cracks at the center of the reactive aggregates in real field concrete structures. First, the surface roughness and the chemical composition of ASR products were examined by Scanning Electron Scanning (SEM) and Energy Dispersive X-ray spectroscopy (EDS). Finally, the viscous behaviour of crystalline ASR products was characterized by performing load-relaxation tests by microindentation, providing new knowledge on the relaxation behaviour of the ASR crystalline products which was about 40%. Furthermore, nanoindentation test were also carried out to better understand the possible length-scale effect. In spite of the large scatter, the characterization at lower scale by nanoindentation showed that the ASR rosette crystals have a greater modulus and lower relaxation rate. This is likely due to the fact that the volume probed by nanoindentation is close to the size of ASR crystals and related interfaces. Finally, a simplified rheological model was employed to estimate the viscosity and characteristic time of the ASR crystalline products. The present result provide new knowledge on the viscous behaviour ASR products which can be helpful for better understanding ASR products and improve existing multiscale models.